Experience in teaching and learning group work among counsellor educators and counselling trainees - Mohamad Yusoff, Salmah (2018)
This research aims to explore the experiences of counsellor educators and counselling trainees of teaching and learning group work. Group work is one of the core courses that aims to prepare trainee counsellors to be group work leaders. However, there is no specific research that explores the preparation of counselling trainees for group work practice from both trainees’ and educators’ perspectives. In this qualitative study, the counsellor educators’ and counselling trainees’ experiences of teaching and learning group work courses are explored. As a collective case study, in-depth exploratory data was collected from six group work lecturers and six groups of undergraduate counselling trainees from three Malaysian public universities and analysed using thematic analysis. The analysis highlighted three important components, which are: 1) experiential learning activities, 2) therapeutic factors in group work training, 3) personal qualities in relation to teaching and learning group work and 4) the interaction of experiential learning activities, personal qualities and therapeutic factors during the teaching and learning group work. These elements are interrelated in the process of understanding both educators’ and trainees’ experiences to promote the best practices in teaching and learning group work courses, especially for informing counsellor educators about the process of teaching and learning group work in counsellor education.